Strategies for Preventing Sexual Violence against Children Based on Islamic Law in Lampung Province - Sulastri, Sulastri; Khairani; Mulhama, Siti Sholehah Alfi (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung, 2024)
Sexual violence against children is a global problem that requires the role of Islamic law in its prevention, starting from the formation of a healthy family to education in the family. This study aims to formulate strategies to prevent sexual violence against children based on Islamic law, using qualitative methods. The research subjects involved individuals involved in sexual violence cases in 8 districts/cities throughout Lampung Province. Data were collected through interviews, documentation, and Focus Group Discussions (FGDs), with analysis using the Miles and Huberman model and data triangulation. The results showed that prevention strategies include child-based education, health, law, and social community, working with religious leaders and recitation groups. However, these strategies have not been effective in reducing the rate of sexual violence against children. Therefore, a more comprehensive Islamic law-based strategy is needed, covering child protection from the womb to adulthood, parenting, education, and choosing the right partner. Recommendation: Stronger collaboration between families, communities and authorities is needed to raise legal awareness of children's rights and tackle child sexual abuse more effectively.